An Integrated Approach to Strategic Asset Management - Brown, Kerry; Laue, M.; Tafur, J.; Mahmood, M.; Scherrer, P.; Keast, R. (Springer, 2014)
This chapter focuses on identifying and analysing the elements of Strategic Management for infrastructure and engineering assets and asks: what are the considerations and implications for adopting and implementing an integrated strategic asset management framework? We contend that corporate governance, policy, objectives and strategy as well as interagency collaboration should be considered as elements in a ‘staged approach’ to understanding how assets are managed within organisations. This will allow for a more comprehensive framework for engineering asset management that considers social and contextual elements. Asset governance details the policies and processes needed to acquire, utilise, maintain and account for an organisation’s assets. It stems from corporate governance principles and defines the management context in which engineering asset managementis implemented. This will be examined to determine the appropriate relationship between organisational strategic management and strategic asset management to further the theoretical engagement with the maturity of strategy, policy and governance for infrastructure and engineered assets. The chapter draws on a document analysis of corporate reports and policy recommendations in terms of infrastructure and engineered assets. The chapter concludes that incorporating an integrated asset management framework can promote a more robust conceptualisation of public assets and how they combine to provide a comprehensive system of service outcomes.